Scholarly Success of Orthopaedic Surgeons Participating in Traveling Fellowships - Theodore Quan, MD; Kevin Yoon, BS; Mumin Sabha, BS; Lancelot Benn, MD; Hamid Hassanzadeh, MD; Addisu Mesfin, MD, FAOA (JBJS Open Access)
Background:. Orthopaedic traveling fellowship programs provide surgeons with valuable opportunities for professional growth and specialized learning. However, there has been limited research on the impact of such programs on scholarly success and career advancement. The aim of this study was to evaluate the demographic, academic, and scholarly outcomes of traveling fellowship participants. Methods:. This study was a retrospective analysis of orthopaedic surgeons who participated in a traveling fellowship program from 1989 to 2024. Demographic and academic characteristics were collected for each traveling fellowship recipient, including residency program attended, fellowship specialty, fellowship institution, academic rank, current practice environment, and leadership roles. The Scopus database was used to determine individual H-indices and number of publications. Other characteristics included board position in a major orthopaedic society, National Institutes of Health (NIH) research funding, Orthopaedic Research and Education Foundation (OREF) grant recipient, advanced degrees, and editorial board position in an orthopaedic journal. Descriptive and regression statistics were used for the study. Results:. Of the 558 physicians who participated in an orthopaedic traveling fellowship, demographic and academic information was available for 506 of them (90.7%). Of these, the majority (96.6%) only completed 1 traveling fellowship. Predominantly, recipients were male (90.7%) and White (79.1%) and had completed a sports fellowship (33.0%). Current practicing environment was often academic (76.5%), with most holding the rank of professor (51.0%). Seventy-two participants (14.2%) had a leadership role as chair and 48 (9.5%) were division chiefs. Participants had an average H-index of 35.7 and averaged 169.9 publications. One hundred seventy-three fellowship recipients (34.2%) received an OREF grant and 67 (13.2%) received NIH research funding. Fellowship participants who received an OREF grant or NIH funding were more likely to have a higher faculty rank, higher H-index, and an increase in the number of publications (p < 0.001 for all). Conclusion:. The lessons, skills, and knowledge from traveling fellowships appear to play an important role in shaping the academic and scholarly career of orthopaedic surgeons. Level of Evidence:. Level IV. See Instructions for Authors for a complete description of levels of evidence.